ESTIMATION OF THE EFFECT OF VARIOUS METHODS AND DEVICES OF IMPULSE OVERVOLTAGE PROTECTION IN THE OIL FIELD ELECTRIC NETWORK 6–10 kV - Sergey V. Sidorov; Valery V. Sushkov; Ilya S. Sukhachev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Relevance. One of the main causes of high accident rate and outages in distributed power supply systems of 6–10 kV oil fields are overvoltages due to lightning effects. The overwhelming number of lightning outages in distribution networks of 6–10 kV, associated with overvoltages, is caused by insufficient level of impulse durability of linear insulation, which leads to the insulator overlap and later to de-energizing of oilfield consumers. To ensure the required lightning resistance of the distributed power supply system for oil fields, various methods are used to install protection devices: non-linear surge arresters, arresters of various types. In this case, the protection devices change the electrical characteristics of the distribution network, which affects the characteristics of transitional processing lightning effects. Therefore, it is necessary to estimate the effect of the most frequently used protective devices on overvoltage in a distributed power supply system for oil fields during lightning effects. The main aim of the research is to estimate the impact of protection devices on overvoltage levels in electric networks of 6 (10) kV of an oil and gas extraction enterprise during lightning effects. Methods. The authors have estimated the influence of protection devices on overvoltage levels by analyzing the transitional process and frequency characteristics for a part of the power supply system on a lightning effect using the algorithms of the Linear Analysis Tools in MATLAB Simulink. Results. The authors determined the dependence of overvoltage level on the type of protective devices and obtained the frequency and time characteristics of the input overvoltage of the consumers, which should be known when choosing protection devices. The dependence of the resonance frequencies on the installed spark gaps is determined. The authors developed in the MATLAB Simulink the simulation model of a typical part of a distributed power supply system of an oil and gas extraction enterprise in Western Siberia, including a non-linear surge arrester, arrester and lightning impulse. The activities to protect oil fields consumers from impulse overvoltages were proposed.